2008
DOI: 10.1007/s00248-007-9349-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Cecal Microbiota of Domestic and Wild Turkeys

Abstract: The extent to which production methods alter intestinal microbial communities of livestock is currently unknown. As the intestinal microbiota may affect animal health, nutrition, and food safety, a baseline comparison of the cecal communities of domestic and wild turkeys was performed. Oligonucleotide fingerprinting of ribosomal RNA (rRNA) genes (OFRG) of 2,990 16S rRNA clones and dot blot quantification of dominant populations were used to identify the dominant bacterial taxa. Seventy-three percent of all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
87
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 47 publications
14
87
0
Order By: Relevance
“…Our study described the presence of a higher number of bacteria in the gut of a wild bird than those reported by previous studies for the gut of birds, some mammals, and even humans [16,22,32,34,62]. Because the analysis we used not only eliminated sequences that include chimera, homopolymer sequences, and sequences created by errors of pyrosequencing [56], but also it removed some real bacterial sequences by its stringent criteria, we expect the total number of OTUs present in the House Sparrow's gut to be higher.…”
Section: Discussionsupporting
confidence: 48%
“…Our study described the presence of a higher number of bacteria in the gut of a wild bird than those reported by previous studies for the gut of birds, some mammals, and even humans [16,22,32,34,62]. Because the analysis we used not only eliminated sequences that include chimera, homopolymer sequences, and sequences created by errors of pyrosequencing [56], but also it removed some real bacterial sequences by its stringent criteria, we expect the total number of OTUs present in the House Sparrow's gut to be higher.…”
Section: Discussionsupporting
confidence: 48%
“…Our results complement a limited number of previous 16S rRNA gene sequence-based comparisons of gut microbiotas in wild and domesticated animals. Analysis of wild and domesticated mice (Wilson et al, 2006), turkeys (Scupham et al, 2008), parrots (Xenoulis et al, 2010), fruitflies (Cox and Gilmore, 2007) and hydra (Fraune and Bosch, 2007) indicate that members of the same species tend to possess gut bacterial communities of similar taxonomic composition at the phylum or class level regardless of domestication status, with some differences between wild and domestic individuals emerging at shallower phylogenetic resolution. These previous studies have revealed varying effects of domestication on gut bacterial diversity, with increased diversity in wild mice (Wilson et al, 2006) and fruitflies (Cox and Gilmore, 2007) compared with domesticated controls, and decreased diversity in wild versus domesticated parrots (Xenoulis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We included sequences from the Zebra, Horse, Wild Ass, Banteng, Indian and Black Rhinoceros, Capybara, Gazelle, Giraffe, Okapi, Kangaroo, Springbok, Takin and Sheep all from . We also included sequences from other studies that satisfied the inclusion criteria of sequence length 4500 bp, and data sets containing 450 sequences from each particular host species, these included: sequences from the dairy cow rumen (Chin EC, Lim WJ, Kim H and Yun HD unpublished data available in the GenBank database); sequences from cow manure (Nakai Y and Yamamoto N, unpublished data available in the GenBank database), sequences from the chicken cecum (Massias B, Urdaci MC unpublished data available in the GenBank database), sequences from Turkey cecum (Scupham et al, 2008) and Hoatzin clone sequences (Godoy-Vitorino et al, 2008). The hoatzin and cow G2Chip OTUs, correspond to the representative sequences of the OTUs detected by the PhyloChip through hybridization with foregut and hindgut DNA from the wild Venezuelan Hoatzins and pasturing cows (this study).…”
Section: Discussionmentioning
confidence: 99%